Variation of Metagenome From Feedstock to Digestate in Full-Scale Biogas Plants - Jiang, Fan; Wang, Sen; Zhang, Yan; Ma, Shichun; Huang, Yan; Fan, Hui; Li, Qiang; Wang, Hengchao; Wang, Anqi; Liu, Hangwei; Cheng, Lei; Deng, Yu; et al. (Frontiers in Microbiology, 2021)
Anaerobic digestion (AD) has been widely used to resolve the problem of organic wastes worldwide. Previous studies showed that the types of feedstock have a great influence on the AD microbiome, and a huge number of AD populations are migrated from upstream feedstocks. However, the changes of microbial compositions from feedstock to AD digestate are still less understood. We collected feedstock samples from 56 full-scale biogas plants, generated 1,716 Gb feedstock metagenomic data in total, and constructed the first comprehensive microbial gene catalog of feedstock containing 25.2 million genes. Our result indicated that the predominant phyla in feedstock are Firmicutes, Bacteroidetes, and Proteobacteria, which is similar to that in AD digestate, and the microbial diversity of feedstock samples is higher than that of AD digestate samples. In addition, the relative abundance of most genes involved in methanogenesis increase from feedstock to AD digestate. Besides, the amount of antibiotic resistance genes (ARGs) and pathogenic bacteria in AD are effectively reduced compared to feedstocks. This study provides a comprehensive microbial gene catalog of feedstock, and deepens the understanding of variation of microbial communities from feedstock to AD digestate of full-scale AD. The results also suggest the potential of AD to reduce the level of ARGs and pathogens in animal manure.